Caravaggio the complete works - Schutze, Sebastian (Taschen, 2017)
"This book gives a comprehensive overview of Caravaggio's entire output with a critical catalogue og his work. Each one of his paintings is presented in fresh contemporary photographs of the highest quality, through which the viewer comes face-to-face with his ingenious repertoire of facial expressions and gestures." -- Provided by publisher